Pembuatan Company Profile Sistem Informasi Gajah Putih (SIGATI) Surakarta Berbasis Website - Puspitasari, Norma; Pamungkas, Canggih Ajika; Anggraheni, Norhisma Zulfani (Jurnal Informa : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
Gajah Putih is a climate village located in Karangasem Village, Laweyan, Surakarta City. This village is one of the locations of the climate village program that is considered successful because it has received a certificate as a location of the Main Category Climate Village Program from the Ministry of Environment and Forestry in 2019. However, this village has not been optimized to convey information to the outside community. The village does not yet have a medium to efficiently convey information and education to the community, especially for people outside the area, making it difficult for people to find information about programs, activities and interesting activities that are running in this village. So far, to find complete information about the programs and activities being carried out by Gajah Putih, outsiders are still required to come directly to the location of this climate village. In this research, the method used is the Waterfall method which consists of five stages, namely: Needs Analysis, System Design, Coding, Testing or Implementation, and Maintenance. With this website-based company profile, it will be beneficial for Gajah Putih Village, because it is a medium of information between Gajah Putih and the community. This company profile was built using the PHP programming language and MySQL as a data delivery medium and the web server is localhost PHP Myadmin.